Conversion Surgery for Pancreatic Cancer—The Impact of Neoadjuvant Treatment - Klaiber, Ulla; Hackert, Thilo (Frontiers in Oncology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) has still a dismal prognosis, mainly because only 15–20% of all patients present with resectable tumor stages at the time of diagnosis. Due to locally extended tumor growth or distant metastases upfront resection is not reasonable in the majority of patients. Considerably, PDAC will be the 2nd most frequent cause of cancer-related deaths within the next 10 years for both men and women. While there is currently no convincing evidence for the use of neoadjuvant therapy in resectable PDAC, there are controversial results from studies investigating neoadjuvant treatment concepts in borderline resectable PDAC (BR-PDAC). However, the definition of BR-PDAC is a topic of debate. While BR-PDAC has originally been defined on merely anatomical criteria, the International Association of Pancreatology (IAP) has recently suggested a broader definition based on a combination of anatomical (A) findings, biological (B) criteria (which reflect tumor aggressiveness), and conditional (C) aspects (which respect host-related condition). In case of BR-PDAC with venous invasion alone, upfront resection is generally recommended whenever technically possible in patients fit for surgery and without evidence for lymph node metastases. In contrast, in case of arterial invasion neoadjuvant therapy is regarded as the treatment of choice. The same accounts for high CA 19-9 levels, suspected or proven lymph node involvement and poor performance status. In locally advanced PDAC (LA-PDAC), neoadjuvant treatment represents the standard of care resulting in proportionally high rates of secondary resection. This “conversion” surgery offers the chance for improved survival times in an otherwise palliative situation. Herein, we summarize the current evidence of different treatment strategies for pancreatic cancer with a focus on conversion surgery and the impact of neoadjuvant treatment in this setting.